Incentive theory for a participatory crowdsourcing project in a developing country - Elizabeth Bosha (South African Journal of Information Management, 2017)
Background: Urbanisation has put enormous strain on the limited resources and services provided by city management. This means that the city must find new ways to manage their resources more effectively. One option is to collect data in a smart city from the citizens in order to make better decisions about resource management.